1999
DOI: 10.1002/jlb.65.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Systemic suppression of human peripheral blood phagocytic leukocytes after whole-body UVB irradiation

Abstract: We examined systemic effects of wholebody UVB irradiation on human peripheral blood phagocytes. We found that 24 h after a single erythemal dose of UVB radiation two phagocyte functions, adhesion and phagocytosis, were reduced by 50%. This functional suppression was accompanied by a significant decrease in the expression of complement receptors (CR1 and CR3) and IgG Fc receptors (FcRII and FcRIII). The greatest reduction (47%) was observed in CR3, which is important for both adhesion and phagocytosis. A kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…Since four of six healthy controls and three of five PLE patients showed the presence of neutrophils in the epidermis 18 h after irradiation (data not shown), however, we hypothesize that once in the tissue, the migration capacity of the neutrophils is similar in PLE patients and healthy controls. Leino et al (1999) showed reduction in the phagocytosis and adhesive function of leukocytes in healthy human volunteers after whole-body irradiation with UVB, possibly due to downregulation of cellsurface receptors. Furthermore, de la Fuente et al (2001) showed both decreased phagocytosis and IL-8 induced chemotaxis in polymorphonuclear cells of patients with systemic lupus erythematosus (SLE).…”
Section: Discussionmentioning
confidence: 96%
“…Since four of six healthy controls and three of five PLE patients showed the presence of neutrophils in the epidermis 18 h after irradiation (data not shown), however, we hypothesize that once in the tissue, the migration capacity of the neutrophils is similar in PLE patients and healthy controls. Leino et al (1999) showed reduction in the phagocytosis and adhesive function of leukocytes in healthy human volunteers after whole-body irradiation with UVB, possibly due to downregulation of cellsurface receptors. Furthermore, de la Fuente et al (2001) showed both decreased phagocytosis and IL-8 induced chemotaxis in polymorphonuclear cells of patients with systemic lupus erythematosus (SLE).…”
Section: Discussionmentioning
confidence: 96%
“…Basophils and eosinophils also have a multilobed nucleus and express CD11b and CD15, but they are not known to infiltrate UVB-exposed normal human skin (24), and by means of specific mAbs we demonstrated that these two cell types are absent in irradiated skin. It has been reported that UVB radiation can cause a considerable decrease in the expression of CD11b on neutrophils isolated from peripheral blood (25). Nevertheless, this marker is clearly detectable on infiltrating neutrophils in UVB-treated skin, as demonstrated by immunohistochemistry.…”
Section: Figure 6 Depletion Of Cd15mentioning
confidence: 89%
“…Similarly, UV-B radiation also suppressed the immunity of the roach (Rutilus rutilus) in terms of suppressed macrophage migration and respiratory burst activities, indicating that UV-B has the potency to suppress the functioning of phagocytes (Salo et al 1998). Systemic effects of whole-body UV-B irradiation on human peripheral blood phagocytes was studied and it was found that 24 h after a single dose of UV-B radiation, two phagocytic functions, i.e., adhesion and phagocytosis were reduced by 50% (Leino et al 1999). The effects of short-term exposure to UV-B radiation on lymphocyte-related parameters were studied under controlled laboratory conditions using roach (Rutilus rutilus), a cyprinid teleost, as the model fish.…”
Section: Discussionmentioning
confidence: 99%